Decision Support Systems V – Big Data Analytics for Decision Making: First International Conference, ICDSST 2015, Belgrade, Serbia, May 27-29, 2015, Proceedings - Delibašić, B (Springer, 2015)
This book constitutes the refereed proceedings of the First International Conference on Decision Support Systems Technology, ICDSST 2015, held in Belgrade, Serbia, in May 2015. The theme of the event was “Big Data Analytics for Decision-Making” and it was organized by the EURO (Association of European Operational Research Societies) working group of Decision Support Systems (EWG-DSS).